IMPLEMENTATION OF GREEN BANKING ON PROFITABILITY AT PT BANK NEGARA INDONESIA (PERSERO) TBK FOR THE 2021–2023 PERIOD - Maharani, Yunita (Fakultas Ekonomi dan Bisnis, Universitas Bangka Belitung, 2025)
Green banking constitutes a strategic initiative aimed at fostering environmentally sustainable practices and mitigating the carbon footprint generated by banking operations. PT Bank Negara Indonesia (BNI), as one of Indonesia’s prominent financial institutions, has incorporated green banking initiatives into its operational framework as a tangible demonstration of its commitment to supporting the government’s national zero-carbon emission agenda. This study seeks to investigate the influence of green banking implementation on bank profitability, with a particular emphasis on the Return On Equity (ROE) ratio as a key financial performance indicator. The research adopts a qualitative methodology utilizing descriptive analysis, with data obtained from secondary sources in the form of the bank’s published annual reports. The results reveal that Bank BNI has actively advanced the green economy agenda in Indonesia through its consistent application of green banking initiatives throughout the 2021–2023 period. These initiatives have made a positive contribution to the enhancement of bank profitability, as evidenced by increased ROE and improved operational efficiency, alongside the integration of climate risk management frameworks in alignment with the institution’s long-term objective of achieving Net Zero Emission by 2060.